2011
DOI: 10.1016/j.ejpain.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

End‐of‐life opioid administration on neonatal and pediatric intensive care units: Nurses' attitudes and practice

Abstract: End-of-life opioid administration to primary comfort care patients in the DR differs fundamentally from NICU or PICU handling of dying patients. Once patients are admitted to an intensive care unit, practice and attitudes towards end-of-life opioid administration are similar in NICUs and PICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
(28 reference statements)
0
12
0
1
Order By: Relevance
“…These findings are contradictory to those of Garten et al who demonstrated that 75% of NICU nurses surveyed believe that regular pain assessment should be performed throughout the dying process. 23 Furthermore, NICU nurses strongly believe that providing pain relief should be a priority during the dying process. 24 Lack of documentation may have partly been a function of the flurry of activities surrounding the infant’s entry into EOL care.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are contradictory to those of Garten et al who demonstrated that 75% of NICU nurses surveyed believe that regular pain assessment should be performed throughout the dying process. 23 Furthermore, NICU nurses strongly believe that providing pain relief should be a priority during the dying process. 24 Lack of documentation may have partly been a function of the flurry of activities surrounding the infant’s entry into EOL care.…”
Section: Discussionmentioning
confidence: 99%
“…The second classification system used was based upon classifications of (neonatal) intensive care patients by Garten et al ( 14 ), Stephens et al ( 15 ), and Verhagen et al ( 16 ):…”
Section: Methodsmentioning
confidence: 99%
“…Other studies similarly found that there was no difference in birth weight or gestational age in whether or not infants received medications for symptoms as part of EOL care and that the vast majority of patients who died in the delivery room did not receive opioids (39). A study of 171 neonates at a level III NICU showed that 27.5% did not receive opioids or benzodiazepines for EOL care (17).…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…Historically, providers have been hesitant to administer medications, specifically opioids and benzodiazepines, out of concern that they will hasten death. This concern of providing medications that have respiratory depression as a side effect in a medically fragile neonate has led to inadequate treatment of symptoms (39). However, there is a commonly accepted ethical notion known as the principle of double-effect which states that an action is justifiable if the nature of the act is good, the good effects are the intended effects as opposed to the bad effects, and that the good effects outweigh the bad given the circumstances (20,47).…”
Section: Pharmacological Managementmentioning
confidence: 99%